The Educational Risk by Luigi Giussani A challenge for both the educator and the learner - Imbimbo, Margherita (Formazione & insegnamento, 2015)
In the present paper we are going to explore the notion of educational risk, following the approach outlined by Luigi Giussani as a possibile way to answer the challenges of modern society, which wavers between the temptation to consider education as not necessary and the urgent need to find strong reference points for an educational theory which is able to develop and carry out human freedom. The educational relation is, first of all, the meeting between two freedoms, where the educator’s self gets involved with the other’s one: in this hazard everyone risks his own freedom. According to Giussani, it is in this risk that we can find the essence of a true education which, therefore, teaches both the educator and the learner to use their freedom properly. On the other side, however, it is just through the risk of confrontation that a structured personality is sheped in the youth and that his freedom comes true. We can start from the notions of educational risk, freedom and responsibility to find one of the possible answer to both usefulness and epistemological features of pedagogy, which must be based not on abstract concepts but on the living reality of the human being.